Effect of ‐OMe Substituent on Salicylaldehyde Schiff Base to Influence the Zn2+ Sensitivity and the Cancer Cell Line Imaging. Issue 27 (17th July 2019) - Dey, Sunanda; Pal, Kunal; Jana, Kuladip; Sinha, Chittaranjan
Abstract: Functional group of a molecule monitors the chemical selectivity and the structure regulates the rate of the reaction. Thus, structure‐function relation controls the overall sensitivity of the chemosensor. In this work, three congeneric Schiff bases with common amine, 2, 2 / ‐(propane‐1, 2‐diylbis(oxy))dianiline with methoxy substituted Salicylaldehyde are synthesised and have been used to examine the selectivity and sensitivity to the metal ions in 9:1 (v/v) acetonitrile/water (10 mM HEPES buffer, pH 7.4) medium. The probes display prominent fluorescence turn‐on emission when bonded with Zn 2+ over sixteen other metal ions with very low limit of detection (LOD), 2.2 to 12.3 nM. Structure with bulkiness has low sensitivity to Zn 2+ which may be due to steric crowding about the binding centres of the chelating motif. The selectivity for Zn 2+ ion may ascribe to chelation enhancement of fluorescence (CHEF) effect. The probes are characterized by 1 H and 13 C NMR, IR, HR‐MS and elemental analysis. The metal: ligand ratio of the Zn(II)‐complexes follows 1:1 molar ratio and has been established by Job's plot, Benesi–Hildebrand plot and HR‐MS data. All the probes have been successfully applied to the detection of intracellular Zn 2+ ion in Human liver cancer cell line, HepG2. Abstract : Three new Schiff bases exhibits emission (λem, 473‐552 nm) upon binding with Zn 2+ ion in CH3 CN/H2 O (9:1 v/v, HEPES buffer, pH 7.4) in presence of sixteen other biologically important metal ions with LOD, 2.2‐12.3 nM. The 1:1, metal:ligand compositions are supported by ESI‐MS, Job's plot and 1 H NMR experimental measurement. Intracellular Zn 2+ ion is detected using the probes in HepG2 Cells (Human liver cancer cell line) under fluorescence microscope.